Development of bivalent cation selective ion exchange membranes by varying molecular weight of polyaniline. (10th March 2015) - Farrokhzad, H.; Darvishmanesh, S.; Genduso, G.; Van Gerven, T.; Van der Bruggen, B.
Abstract: A novel hybrid cation exchange membrane (CEM) composed of a blend of polyvinylidene fluoride (PVDF), sulfonated PVDF(S-PVDF) and doped polyaniline (PANi) as additive was prepared. PANi was synthesized with different molecular weights to optimize the performance of membranes for water softening. The membrane properties such as thermal behavior, membrane structure, membrane morphology and miscibility, ion exchange capacity (IEC), permselectivity, water uptake, contact angle, cell resistivity, current efficiency and electrodialysis (ED) performance were evaluated. Addition of doped PANi increased the bivalent selectivity of the cation exchange membrane. The highest bivalent selectivity and best removal of Ca 2+ and Mg 2+ were achieved for PANi with Mw  ≈ 45, 000 g mol −1 and polydispersity index (PDI) ≈ 3.2.